Influence of Earnings per Share and Price to Earnings Ratio on Stock Price: A Study on PT. Astra International Tbk in 2020–2024 Period - Irwin Ananta Vidada; Saridawati Saridawati; Raden Muhammad Tedy Aliudin; Agung Suprianto; Etika Sabariah (Manunggal Halim Jaya, 2026)
This study examines the impact of earnings per share (EPS) and price-to-earnings ratio (P/E ratio) on the stock price of PT Astra International Tbk during the 2020–2024 period. Addressing the research gap in post-pandemic valuation studies within Indonesia's automotive sector, this research employs a quantitative approach using quarterly secondary data obtained from official financial reports and stock market records. Classical assumption tests confirm that the regression model satisfies the criteria for normality, multicollinearity, heteroskedasticity, and autocorrelation, ensuring the robustness of the analysis. The results demonstrate that both EPS and PER have a positive and significant impact on stock prices, indicating that profitability and valuation measures are critical determinants of market value. These findings underscore the importance of fundamental analysis in informing investment decisions and provide empirical evidence for investors and financial analysts seeking to assess corporate performance in emerging markets.